MEANING AND IMPORTANCE OF COLORS IN PAINTING: SYMBOLICALLY: चित्रकला में रंगों का अर्थ एवं महत्व: प्रतीकात्मक रूप में - Pratima (International Journal of Research -GRANTHAALAYAH, 2014)
Character balance means the orderly combination of characters in a picture. That is, color is a big subject in painting and the combination of colors in the picture is very important. The importance of colors in Indian painting has been from prehistoric times to modern times. The inspiration of the artist's inner expressions in the painting is displayed through paintings. Art takes birth in the painter's emotions. It develops only from unconscious unknown depths of mind. Picture has been an important medium in transforming these feelings into realization. Colors have their own distinct significance, as well as colors have their own expressions and language, they have a deep connection with human emotions. In the Indian aesthetic philosophy, the colors described in the pictures have different meanings, such as white color symbolizes peace and satvikta, red symbolizes valor and valor, black evils and mental instincts. The medium of use of colors in painting has varied from prehistoric times to modern times, such as natural color, mineral color, acrylic color, watercolor etc. Till date, paints have been filled in the paintings by the painter in all these mediums. Examples of this include the fresco depiction style in Ajanta, the Mughal period hill, Rajasthani tempra, Renaissance period waters, etc. Using the above colors in the paintings, the picture depicts the beauty, elegance and emotion, the artist who is inspired by the very passion and inspiration, displays the colors through different pictures. Color stimulates the painter's expressions in the picture. Under the publication of "Indian Society of Oriental Art" by Avanindranath Thakur for the knowledge of art renaissance and picture-making, in reference to 'Alakhri painting' in the fourth place among the 64 arts mentioned in 'Kamasutra' in the booklet 'Shadang'. Detailed discussion is made about the six limbs. In these six organs, importance is shown in the sixth order of the alphabet, i.e. the color picture. In this, the knowledge of full color combination depicted by the painter, their symbolic, detailed interpretation of meaning and rules. Similarly, it has been said in the Natyasastra - 'Varnaam tu vidhim gatva and prakritimeva ch kuryadangasya rachanam', that is, by understanding the method and nature of the varna, the figure should be formed. With this, the development of art skills in the artist and the viewer realizes the importance of colors in the painting. वर्ण संतुलन का अर्थ चित्र में वर्णों का सुव्यवस्थित संयोजन। अर्थात् चित्रकला में रंग एक बड़ा विषय है और चित्र में रंगों की संयोजना बहुत ही महत्वपूर्ण है। भारतीय चित्रकला में रंगों का महत्व प्रागैतिहासिक काल से लेकर आधुनिक काल तक रहा है। चित्रकला में कलाकार के आंतरिक भावों की अभिप्रेरणा चित्रों के माध्यम से प्रदर्शित होती है। कला चित्रकार के मनोभावों में जन्म लेती है। यह मन की अचेतन अज्ञात गहराईयों से ही विकसित होती है। इन भावनाओं को साकार रूप में परिवर्तित करने में चित्र महत्वपूर्ण माध्यम रहा है। रंगांे का अपना ही अलग महत्व रहा है इसके साथ ही रंगों की अपनी भावभंगिमा व भाषा होती है, इनका मानवीय भावनाओं से गहरा संबंध होता है। भारतीय सौन्दर्य-दर्शन में चित्रों में वर्णित रंगों का अर्थ अलग-अलग है, जैसे- सफेद रंग शांति और सात्विकता का प्रतीक, लाल शौर्य और वीरता का प्रतीक, काला बुराईयों व मानसिक वृत्तियों इत्यादि। चित्रकला में प्रागैतिहासिक काल से लेकर आधुनिक काल तक रंगों के प्रयोग का माध्यम भिन्न-भिन्न रहा है, जैसे- प्राकृतिक रंग, खनिज रंग, एक्रेलिक रंग, जलरंग आदि। अभी तक इन सभी माध्यमों में चित्रकार द्वारा चित्रों में रंग भरे जाते रहे हैं। इसके उदाहरणों में अजन्ता में फ्रेस्को चित्रण शैली, मुगलकालीन पहाड़ी, राजस्थानी टेम्परा, पुनर्जागरणकाल जलरंग आदि। चित्रों में उपर्युुक्त रंगों का प्रयोग कर चित्र में सौन्दर्य, लावण्य व भावों का निरूपण होता है, जिस कलाकार बहुत ही तन्मयता व अंतःप्रेरणा से प्रेरित हो रंगों को विभिन्न चित्रों के माध्यम से प्रदर्शित करता है। रंग चित्र में चित्रकार के भावों को उदीप्त करता है। अवनीन्द्रनाथ ठाकुर द्वारा कला के पुनर्जागरण व चित्र-सृजन के ज्ञान हेतु “इण्डियन सोसायटी आॅफ ओरिएन्टल आर्ट” के प्रकाशन के अंतर्गत ‘षडांग’ नामक पुस्तिका में ‘कामसूत्र’ में वर्णित 64 कलाओं में चैथे स्थान पर ‘आलेख्य चित्रकला’ के सन्दर्भ में चित्रकला के छः अंगों के बारे में विस्तृत विवेचना की है। इन छः अंगों में छठे क्रम में वर्णिकाभंग अर्थात् रंगों के चित्र में महत्व को दर्शाया गया है। इसमें चित्रकार द्वारा चित्रण पूर्ण रंग संयोजन का ज्ञान, उनकी प्रतीकात्मक, अर्थ व नियमों का विस्तृत विवेचन है। इसी प्रकार नाट्यशास्त्र में कहा गया है कि- ‘वर्णनाम तु विधिम् गत्वा तथा प्रकृतिमेव च कुर्यादंगस्य रचनाम्’, अर्थात् वर्ण की विधि और प्रकृति को समझकर ही आकृति को बनाना चाहिए। इससे कलाकार में कला-कौशल का विकास व दर्शक को चित्रकला में रंगों के महत्व का बोध होता है।